2022
DOI: 10.1111/1759-7714.14333
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer risk prediction models based on pulmonary nodules: A systematic review

Abstract: Background: Screening with low-dose computed tomography (LDCT) is an efficient way to detect lung cancer at an earlier stage, but has a high false-positive rate. Several pulmonary nodules risk prediction models were developed to solve the problem. This systematic review aimed to compare the quality and accuracy of these models. Methods: The keywords "lung cancer," "lung neoplasms," "lung tumor," "risk," "lung carcinoma" "risk," "predict," "assessment," and "nodule" were used to identify relevant articles publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 65 publications
1
22
0
1
Order By: Relevance
“…Existing models, which are generally based on American and European populations, may be inefficient when applied to Asian populations because of the differences in population characteristics; the validation of these models in our dataset supports this. Models constructed on Chinese and Asian populations may have bias originating from small sample sizes, retrospective study designs, and single data sources 12 . Models based on deep learning algorithms have shown good discrimination, 27–29 but the demand for large numbers of covariates may limit their clinical application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing models, which are generally based on American and European populations, may be inefficient when applied to Asian populations because of the differences in population characteristics; the validation of these models in our dataset supports this. Models constructed on Chinese and Asian populations may have bias originating from small sample sizes, retrospective study designs, and single data sources 12 . Models based on deep learning algorithms have shown good discrimination, 27–29 but the demand for large numbers of covariates may limit their clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…International guidelines recommend the use of prediction models to reduce the FPR of screening 10,11 . However, our previous systematic review suggested that no representative model has been constructed using data from large‐sample, multisource, prospective cohorts in China 12 . At present, the models for the Chinese population are mostly based on small sample, single‐center retrospective research, and extrapolation is limited 13–17 ; existing and widely used models are generally based on European and American populations, 18–23 and may not be appropriate for the screening of Asian and Chinese populations, which have unique demographic characteristics 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Aleksandar Georgiev 1,2 * , Lyubomir Chervenkov 1 , Vania Anastasova 3 , Tanya Kitova 4,5 Dear Editor,…”
Section: Comment On "Evaluation Of Pulmonary Nodules By Magnetic Reso...mentioning
confidence: 99%
“…The majority of diagnosed small pulmonary nodules are incidental findings 3 , and globally more than half of lung cancer patients are diagnosed initially in stage IV or more advanced stage 4 . The free survival rate in stage IV and above according to medical literature is approximately 1 year or less, and 5-year survival rates are close to 0% 5,6 .…”
Section: Comment On "Evaluation Of Pulmonary Nodules By Magnetic Reso...mentioning
confidence: 99%
“…Lung cancer remains the most common cancer and the leading cause of cancer death in China. The overall 5year survival rate of lung cancer is between 10% and 20% in most countries [ 2 ]. The final stage of progression of lung cancer is the unrestrained development and division of abnormal cells [ 3 ].…”
Section: Introductionmentioning
confidence: 99%